Human breast milk isolated lactic acid bacteria: antimicrobial and immunomodulatory activity on the Galleria mellonella burn wound model - Guarnieri, Antonio; Venditti, Noemi; Cutuli, Marco Alfio; Brancazio, Natasha; Salvatore, Giovanna; Magnifico, Irene; Pietrangelo, Laura; Falcone, Marilina; Vergalito, Franca; Nicolosi, Daria; Scarsella, Franco; Davinelli, Sergio; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionManaging burn injuries is a challenge in healthcare. Due to the alarming increase in antibiotic resistance, new prophylactic and therapeutic strategies are being sought. This study aimed to evaluate the potential of live Lactic Acid Bacteria for managing burn infections, using Galleria mellonella larvae as an alternative preclinical animal model and comparing the outcomes with a common antibiotic.MethodsThe antimicrobial activity of LAB isolated from human breast milk was assessed in vitro against Pseudomonas aeruginosa ATCC 27853. Additionally, the immunomodulatory effects of LAB were evaluated in vivo using the G. mellonella burn wound infection model.Results and discussionIn vitro results demonstrated the antimicrobial activity of Lactic Acid Bacteria against P. aeruginosa. In vivo results show that their prophylactic treatment improves, statistically significant, larval survival and modulates the expression of immunity-related genes, Gallerimycin and Relish/NF-κB, strain-dependently. These findings lay the foundation and suggest a promising alternative for burn wound prevention and management, reducing the risk of antibiotic resistance, enhancing immune modulation, and validating the potential G. mellonella as a skin burn wound model.